Two minute warning - Peerce, Larry; Bridges, Beau.; Hassett, Marilyn; Janssen, David; Klugman, Jack.; Rowlands, Gena.; Heston, Charlton; LaFountaine, George; Balsam, Martin; Cassavetes, John.; Pidgen, Walter (Culver City, CA : Universal Studios, 1976)
Charlton Heston plays Captain Pete Holly, a hard-boiled cop whose initial investigation of a random shooting(seen at the start) leads him to a championship football game at the LA Coliseum - a sniper is perched above the scoreboard! When the time comes, the sniper will kill a target - or several? WHo is he after?